Sago Wastes as a Feedstock for Biosugar, Precursor for Chemical Substitutes - Mohd A., Jenol; Muhd N., Ahmad; Dayang Salwani, Awang Adeni; Micky, Vincent; Nurashikin, Suhaili (John Wiley & Sons, Inc, 2023)
In Southeast Asia, the sago palm serves as one of the most important starch providers, which has been utilized as food for centuries. In Malaysia specifically in Sarawak, sago starch-based agro-industry is one of the major revenue sources for the state. In contempt of the increasing demand soon, sago industry will eventually be facing new threats related to the waste management problem. The processing of sago palm into starch generates a huge amount of several types of waste, including bark, hampas, wastewater, and sago frond. The utilization of these wastes in the bioconversion of value-added products is deemed a promising approach due to their availability as well as their physicochemical contents. This has led to the exploration of the utilization of sago wastes for various chemical substitutes development, such as biosugar and several bioproducts derivatives ( l -Lactic acid, cellobiose, silage, enzymes, and kojic acid). This chapter aims to discuss and explore the current development of sago waste biorefinery as well as its prospects and challenges. With the exponential development and advancement in current technology, the biorefinery of sago wastes is deemed to be beneficial to the national economy.